Gender analysis of labor force outcomes: Evidence from Cameroon - Jean C. Kouam; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The present study contributes to the extant literature by assessing how financial and human developments moderate the incidence of vulnerable female employment on female labour force participation in Cameroon for the period 1987 to 2020 using the generalized least squares (GLS) estimation approach. Human development and financial development moderating or policy variables are also employed in order to improve space for policy implication. It is apparent from the findings that human development in the perspective of the human development index (HDI) and broad money supply are necessary and sufficient conditions to moderate vulnerable female employment for female labour force participation. Accordingly, HDI thresholds of between 0.591 and 0.634 are needed to reverse to the negative incidence of female vulnerable employment on female labour force participation. Furthermore, a threshold of 30.294 (% of GDP) of broad money supply is also needed to reverse the negative incidence of vulnerable female employment on female labour force participation. Other implications for policy are discussed.
Keywords: G20; I10; I32; O40; O55; 330; Gender: Labor force; Cameroon; Sustainable development